Effectiveness of Spontaneous Pushing versus Valsalva Pushing in the Second Stage of Labor on Maternal and Neonatal Outcomes: A Systematic Review and Meta-analysis - Kownaklai, Jaruwan; Phanwichatkul, Titaree; Chaichan, Atchara; Lee, Amanda (Pacific Rim International Journal of Nursing Research, 2024)
Vaginal birth is a natural process, but maternal pushing is an essential factor in the mechanism and process of delivery. This systematic review examined the evidence comparing the effectiveness of two methods of pushing techniques (spontaneous pushing versus Valsalva pushing) on maternal and neonatal outcomes in the second stage of labor. A literature search of Scopus, PubMed, ScienceDirect, CINAHL, PsycINFO, and ThaiJo for articles published between 2012 and 2023 revealed 12 studies with a focus on maternal pushing during the second stage, but four with neonatal outcomes (APGAR scores) and maternal outcomes (fatigue and duration of labor). Meta-analysis of the four studies did not support the benefit of spontaneous pushing in reducing the duration of labor but did support spontaneous pushing in lessening maternal fatigue two hours postpartum. Spontaneous pushing did not directly benefit the neonatal APGAR scores at 1 or 5 minutes postpartum. The result that spontaneous pushing did not shorten labor was unexpected; this is contrary to other studies that have reported a shorter labor duration. The small number of studies makes it difficult to conclude the effectiveness of either pushing technique. Further evidence is necessary to include possible confounding variables postpartum, including women’s choice, advanced assessments of neonatal outcomes, and maternal recovery beyond the immediate postpartum period.